Pemodelan cerdas disain meja belajar sederhana: Analisis material dengan finite element approach - Ameliyana Rizky Syamara Putri Akhmad Yani; Muhammad Alfin Abdurachim Putra (Jurnal Teknik Mesin Indonesia, 2025)
This study analyzes the strength of study tables using the Finite Element Analysis (FEA) method and explores material variations, including very low-density PE plastic, Ductile iron, and balsa wood. The main focus of this study is on three-dimensional modeling and load-test simulations of 3000 N using a standard fixed-geometry fixture10. The simulation results show that Ductile iron exhibited the minimum deformation (0.051 mm), while balsa wood recorded the second largest (2.070 mm). However, a Factor of Safety (FS) analysis of 1.03 proves that balsa wood possesses adequate strength and a superior strength-to-weight ratio, making it the optimal choice. This study provides important insights into selecting optimal materials for designing sturdy, durable study tables that deliver maximum performance in everyday use.